Classical Ecological Restoration and its Current Challenges: Assisted Migration as an Adaptation Strategy to Climate Change - Gómez-Ruiz, Pilar A. (2017)
Ecological restoration is a very active area in ecology and of great importance for ecosystems management. Despite of being a relatively young discipline, the classical concepts of restoration seem, at present, impractical considering the great challenges generated by modification and destruction of ecosystems. This is due to anthropic activities (deforestation, change of land use, pollution) and global climate change. In the classic definition of restoration, the objective is to recover the degraded ecosystem to the same conditions of a historical reference state. However, nowadays the ecosystems return to a state prior to the disturbances seems unviable, because the thresholds of resilience have already been overcome. Additionally, climate change is causing environmental changes at an unprecedented rate. For this reason, ecological restoration needs to unite efforts of diverse actors to recover ecosystems that can be sustainable and functional in the future, where the species could be able to tolerate the environmental conditions that will exist in the long term. Assisted migration has been proposed as a conservation strategy; it is defined as the translocation of species to new locations outside their known range of distribution. In the current context of loss of diversity and ecosystems, this strategy could be fundamental for the formation of new communities that can later become novel ecosystems where species that are fundamental to the dynamics of ecosystems can persist and, at the same time, recover function, structure and resilience.